Self-Expanding Metallic Stents: Application and Long Term Follow-Up in Patients with Malignant and Benign Obstructive Jaundice - Turhan CUMHUR; Tülay ÖLÇER; A. Sedat BOYACIOĞLU; Ahmet MAVİŞ and Ensar ÖZDEMİR and Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2020)
-